Brahms and the Shaping of Time - Murphy, Scott; Murphy, Scott (Book collections on Project MUSE., 2018)
Inhaltsverzeichnis: Introduction: Brahms, analysis, and time / Scott Murphy -- Setting texts -- Expressive declamation in the songs of Johannes Brahms / Harald Krebs -- Temporal disruptions and shifting levels of discourse in Brahms's Lieder / Heather Platt -- Measuring phrases -- Phrase rhythm and the expression of longing in Brahms's "Gestillte Sehnsucht" op No. 1 / Jan Miyake -- On the oddness of Brahms's five-measure phrases / Samuel Ng -- Recasting hemiolas -- Hemiola as agent of metric resolution in the music of Brahms / Ryan McClelland -- Brahms at twenty: hemiolic varietals and metric malleability in an early sonata / Richard Cohn -- Shifting perspectives -- Containment and wave: temporal experiment in Brahms's opus 2 / Frank Samarotto -- Rhythmic displacement in the fugue of Brahms's Handel variations: the refashioning of a traditional device / Eytan Agmon -- Durational enharmonicism and the opening of Brahms's "Double concerto" / Scott Murphy.